Delineating antibody responses elicited by four SARSCoV-2 variants against the Mu variant - Kgagudi, Prudence (My University, 2024)
SARS-CoV-2 is the causative agent of the acute respiratory syndrome known as coronavirus disease 2019 (COVID-19). The SARS-CoV-2 spike protein plays an essential role in virus attachment, fusion and entry and is the main target of neutralizing antibodies. Continued evolution of the spike has led to the emergence of variants of concern or interest (VOC/VOIs) which pose a greater risk to the population due to augmented transmission risk, increased disease severity, antigenic escape and/or decreased effectiveness of vaccines. The Mu variant was first identified in Columbia in January 2021, however the immune escape potential of the variant remains poorly characterised. It is typified by T95I, Y144S and Y145N mutations in the N-terminal domain; R346K, E484K, and N501Y mutations in the receptor-binding domain and D614G, P681H, and D950N mutations in the S2 region. This study aimed to assess targeting of the Mu variant by neutralizing and non-neutralizing antibodies elicited by four variants during four COVID-19 waves in South Africa namely D614G, Beta, Delta and Omicron (BA.1). This was achieved by measuring antibody binding, neutralization and antibody dependent cellular cytotoxicity (ADCC) activity against Mu, and comparing these responses across each of the four variants tested. All variants elicited cross-reactive binding antibodies to Mu although the magnitude of binding to Mu was reduced. This cross-reactivity was a result of multiple binding antibody epitopes on the spike protein. We observed variable neutralization escape of Mu from antibodies triggered by infection with WT D614G and Delta. Antibodies induced by the Beta variant exhibited increased breadth towards the Mu variant when compared to those elicited by other variants. Neutralization escape of Mu from antibodies elicited by WT D614G and Delta may be caused by the 95I, 484K and 346K mutations in Mu, which are known to confer resistance in other variants. Compared to neutralization, ADCC was mostly preserved against Mu. However, the infecting variant impacted the potency of ADCC responses. WT D614G triggered significantly higher ADCC activity against Mu compared to Beta, Delta and Omicron. These data suggest that different variants trigger qualitatively different neutralizing and Fc effector responses, providing a rationale to study humoral resistance following infection by different variants. As Mu shares mutations with other VOCs, this study may aid in predicting the impact of mutations that may be common to emerging VOCs
A research report submitted in partial fulfilment of the requirement for the degree of Master of Science in Medicine to the Faculty of Health Sciences, University of the Witwatersrand, School of Pathology, Johannesburg, 2023
Keywords: Antibody responses; Variants; Acute respiratory syndrome; SDG-3: Good health and well-being